2006
DOI: 10.1097/01.ta.0000236576.81860.8c
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Based Violence Intervention Programs Work

Abstract: Significant differences exist between the VIP intervention and nonintervention groups in terms of the quantity and severity of criminal activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(135 citation statements)
references
References 8 publications
2
127
0
Order By: Relevance
“…Two studies, however, provided data that allowed generation of estimates. In an RCT, Cooper et al 27 found that the HVIP group was four times less likely to be convicted of violent crime than the control group (13% vs 55%). In a quasi-experimental evaluation, Shibru and colleagues 29 found that the incidence of violent crime perpetration was significantly lower among subjects in the HVIP group than the control group (9% vs 16%).…”
Section: Outcome Estimatesmentioning
confidence: 97%
See 2 more Smart Citations
“…Two studies, however, provided data that allowed generation of estimates. In an RCT, Cooper et al 27 found that the HVIP group was four times less likely to be convicted of violent crime than the control group (13% vs 55%). In a quasi-experimental evaluation, Shibru and colleagues 29 found that the incidence of violent crime perpetration was significantly lower among subjects in the HVIP group than the control group (9% vs 16%).…”
Section: Outcome Estimatesmentioning
confidence: 97%
“…The review of HVIPs suggested that they are effective in preventing violent reinjury. Based on the empirical evidence of HVIPs, 14,[27][28][29] it was estimated that HVIPs reduce the 5-year incidence of violent reinjury by 25%. Therefore, each reinjury outcome estimate for the population without HVIP intervention was multiplied by 0.75 to produce estimates of outcomes with HVIP intervention (e.g., 37.26Â0.75=28.0 for nonfatal violent reinjury resulting in hospitalization).…”
Section: Outcome Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of these factors, conducting a VBI with victims of violent assault is an attractive option, and many of the papers included in this review worked with this population (e.g. Aboutanos et al 2011;Becker et al 2004;Cooper et al 2006;Cunningham et al 2012;De Vos et al 1996;Zun et al 2006). …”
Section: Victimsmentioning
confidence: 99%
“…In a similar study, Cooper et al (2006) used a randomised controlled trial to evaluate an initiative which provided intensive psychosocial follow-up services to repeat victims of violence (Cooper, Eslinger, & Stolley, 2006). Recruitment was again completed in a medical setting.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%